The development of Malay religious magazine in pre-independence Malaysia: a literature review - Annuar Ramadhon Kasa,; Norhayati Hamzah,; Mohd Roslan Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The period of pre-independence Malaysia witnessed distinct phases in the development of religious magazines. The first religious magazine, al-Imam, introduced Islamic reformist ideas inspired by Middle Eastern intellectuals. Subsequent publications, however, adopted different approaches to disseminating Islamic teachings through magazine publishing. Thus, this literature review aims to explore the development of religious magazines between 1906 and 1957, dividing it into two phases which are the pre-World War II period (1906–1941) and the post-World War II period (1945–1957). This article employs a narrative review approach, a form of literature review that seeks to provide a comprehensive overview. It is particularly suited for historical research, as it synthesises existing knowledge from a broad range of secondary sources in a descriptive manner. The review identifies several factors influencing the development of religious magazines, including the rise of the Islamic reform movement, awareness among religious scholars to propagate Islam, the earlier growth of newspapers, the emergence of intellectual groups, and advancements in printing technology. The pre-World War II period exhibited a more dynamic publication landscape, with 24 religious magazines produced compared to only 18 in the post-war period. This decline is due to the shift in Malay societal focus towards politics, leading madrasahs, associations, and clubs to reduce their magazine output in the second phase. Although various factors influenced the publication of religious magazines, a steadfast commitment to religion was the key factor for all types of publishers, contributing significantly to the development of Islamic publication culture during the period.